(untitled) (Bangladesh Rice Journal, 2015)
Forty genotypes of Balam rice germplasm of Bangladesh were studied for 17 morpho-physicochemical characters at BRRI during 2009-11. The cluster analysis using Mahalanobis D2 statistics, grouped the genotypes into seven clusters, where no duplicate germplasm was found for the studied characters. The highest number of genotypes (8) was constellated into clusters I, III and V and the lowest (2) was in cluster IV. The intra- and inter-cluster distances were maximum (1.17 and 21.16) in cluster VII and between clusters II and IV and minimum (0.27 and 2.23) in cluster IV and between clusters II and VII respectively. Based on the values of principal component score, the two-dimensional scatter diagram (Z1-Z2) also distributed the genotypes into seven groups. The genotype of cluster IV, produced the highest flag and penultimate leaf area (1136 cm2), culm diameter (7.2 mm), days to maturity (152 days), primary and secondary branches per panicle (63), grain yield per panicle (4.9 g), 1000-grain weight (29.3 g), grain yield per hill (31.3 g), cooking time (19 min) and amylose content (24.1%). Similarly, the genotype of cluster I, produced the tallest plant (148 cm), maximum straw yield per hill (40.0 g) and protein content (9.6%), while the genotype of cluster VI, produced the highest panicle per plant (21) and the genotype of cluster III, produced the longest grain (8.8 mm). Therefore, it may be possible to obtain the highest mean values for the maximum studied characters, if the genotypes of cluster IV are crossed with the genotypes of cluster I, cluster III and cluster VI respectively. Besides, the canonical variate analysis showed that the grain length, cooking time, straw yield per hill, days to maturity, plant height and grain yield per panicle contributed maximum to the genetic divergence of the studied germplasms. Finally, the study revealed that the Balam rice germplasm can offer a diverse valuable gene reservoir to utilize in hybridization programmes for the improvement of Balam rice. Bangladesh Rice j. 2015, 19(1): 9-15